2000
DOI: 10.1152/jappl.2000.89.5.2099
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Axial stretch increases spontaneous pacemaker activity in rabbit isolated sinoatrial node cells

Abstract: Isolated, spontaneously beating rabbit sinoatrial node cells were subjected to longitudinal stretch, using carbon fibers attached to both ends of the cell. Their electrical behavior was studied simultaneously in current-clamp or voltage-clamp mode using the perforated patch configuration. Moderate stretch ( approximately 7%) caused an increase in spontaneous beating rate (by approximately 5%) and a reduction in maximum diastolic and systolic potentials (by approximately 2.5%), as seen in multicellular preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 24 publications
2
66
0
Order By: Relevance
“…The contribution of I f and its importance as a pharmaceutical target has been proven by the successful development of ivabradine and is delineated further in the review article by DiFrancesco 26 in this review series. Further currents seem to be involved in the depolarization phase (I st , mechanosensitive currents 27 and others) whose relative contributions are still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of I f and its importance as a pharmaceutical target has been proven by the successful development of ivabradine and is delineated further in the review article by DiFrancesco 26 in this review series. Further currents seem to be involved in the depolarization phase (I st , mechanosensitive currents 27 and others) whose relative contributions are still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…One potential limitation of our study is whether the mechanical perturbations may be affecting small numbers of pacemaker cells that may have been present in the cell monolayers (although we isolated cells from only the bottom 70% of the ventricle). It may be argued that the pacemaking ability of these cells would be suppressed by the large electrical load presented by surrounding ventricular cells but that mechanical perturbations may augment the pacemaker activity, as underlies the Bainbridge reflex to stretch and has been observed in isolated sinoatrial nodal tissue (1) and isolated sinoatrial nodal cells (11). However, in the former study, the tissue was stretched by an unspecified length for a period of 5 s, whereas in the latter study cell length was increased by 5-10% of resting length and held for the duration of measurements (time interval unspecified).…”
Section: Discussionmentioning
confidence: 99%
“…This SAC model was described in detail in our recent work (39). Several studies have shown that physical stretch of isolated ventricular myocytes produced stretch-activated currents with a linear current/voltage relationship and reversal potentials between Ϫ6 and Ϫ11 mV (6,48,49). Thus, for the majority of experiments in this study, we set the reversal potential of SAC (E SAC) ϭ Ϫ10 mV and GSAC to a constant value for each recording, but the value of GSAC was varied to investigate the critical GSAC required to induce EADs.…”
Section: Methodsmentioning
confidence: 99%